Eco-friendly surface modification approach to develop thin film nanocomposite membrane with improved desalination and antifouling properties - Khoo, Ying Siew; Lau, Woei Jye; Liang, Y. Y.; Karaman, Mustafa; Gürsoy, Mehmet; Ahmad Fauzi, Ismail (Elsevier B.V., 2021)
Introduction: Nanomaterials aggregation within polyamide (PA) layer of thin film nanocomposite (TFN) membrane is found to be a common issue and can negatively affect membrane filtration performance. Thus, post-treatment on the surface of TFN membrane is one of the strategies to address the problem. Objective: In this study, an eco-friendly surface modification technique based on plasma enhanced chemical vapour deposition (PECVD) was used to deposit hydrophilic acrylic acid (AA) onto the PA surface of TFN membrane with the aims of simultaneously minimizing the PA surface defects caused by nanomaterials incorporation and improving the membrane surface hydrophilicity for reverse osmosis (RO) application. Methods: The TFN membrane was first synthesized by incorporating 0.05 wt% of functionalized titania nanotubes (TNTs) into its PA layer. It was then subjected to 15-s plasma deposition of AA monomer to establish extremely thin hydrophilic layer atop PA nanocomposite layer. PECVD is a promising surface modification method as it offers rapid and solvent-free functionalization for the membranes. Results: The findings clearly showed that the sodium chloride rejection of the plasma-modified TFN membrane was improved with salt passage reduced from 2.43% to 1.50% without significantly altering pure water flux. The AA-modified TFN membrane also exhibited a remarkable antifouling property with higher flux recovery rate (>95%, 5-h filtration using 1000 mg/L sodium alginate solution) compared to the unmodified TFN membrane (85.8%), which is mainly attributed to its enhanced hydrophilicity and smoother surface. Furthermore, the AA-modified TFN membrane also showed higher performance stability throughout 12-h filtration period. Conclusion: The deposition of hydrophilic material on the TFN membrane surface via eco-friendly method is potential to develop a defect-free TFN membrane with enhanced fouling resistance for improved desalination process.